MEMBACA TEMA, MAKNA, SUASANA, DALAM ANTOLOGI AYAT-AYAT API SAPARDI DJOKO DAMONO - Nova Sobariah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2022)
This study aims to describe the inner structure, especially the theme, meaning, and atmosphere contained in the poetry anthology Ayat-Ayat Api by Sapardi Djoko Damono. The poetry anthology of Ayat-Ayat Api is a collection of selected poems in which there are poems set in the events of the New Order era. The method used by the author in this study is a qualitative descriptive method. The data collection technique used was literature, reading, taking notes, and document analysis in the form of the poetry book itself entitled Ayat-Ayat Api by Sapardi Djoko Damono which was published in 2017 by PT Gramedia Pustaka Utama Jakarta. The book has a thickness of 88 pages which is divided into three parts, namely Verse Zero, Verse Watches, and Ayat Api. Data taken from the poetry anthology Ayat-Ayat Api in the form of words, sentences, and poetry quotes that are the keywords of the poem. The results showed that the ten poems analyzed had various themes, meanings, and different atmospheres, including: 1) humanity, 2) social criticism, 3) hope, 4) anxiety, 5) death, 6) divinity, and 7) populist and democracy.